2021
DOI: 10.51791/njap.v48i3.2950
|View full text |Cite
|
Sign up to set email alerts
|

An in-vitro evaluation of the potentials of turmeric as phytogenic feed additive for rumen modification

Abstract: The potential risk to animal and human health in the use of antibiotic feed additives for modifying rumen fermentation has necessitated the search for natural alternatives which are generally regarded as safe. The aim of this study was to evaluate the potentials of turmeric powder in rumen manipulation using the in vitro method. Substrate of Panicum maximum and concentrate in ratio 6: 4 with turmeric inclusion at four levels of 0, 5, 10 and 15 mg/g dry matter (DM) were used for this study. The experiment was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The first case was substantiated by the lower molar proportions of branch chain volatile fatty acids, i.e., end products of the deamination of feed amino acids, in plant supplementation as compared to the control; the second case was supported by the higher MCP concentrations in the supplementation as compared to the control. Moreover, Aderinboye and Olanipekun [37] found that turmeric inclusion above 5 mg/g DM of substrate can modify the rumen by causing a reduction in fermentation end products, and a reduction in ammonia production at 15 mg/g, which significantly reduced microbial biomass, has implications for lowering microbial protein synthesis. In this study, both occurrences were confirmed in the plant materials with high tannin contents.…”
Section: In Vitro Rumen Fermentation Bacteria and Protozoal Population Characteristicsmentioning
confidence: 99%
“…The first case was substantiated by the lower molar proportions of branch chain volatile fatty acids, i.e., end products of the deamination of feed amino acids, in plant supplementation as compared to the control; the second case was supported by the higher MCP concentrations in the supplementation as compared to the control. Moreover, Aderinboye and Olanipekun [37] found that turmeric inclusion above 5 mg/g DM of substrate can modify the rumen by causing a reduction in fermentation end products, and a reduction in ammonia production at 15 mg/g, which significantly reduced microbial biomass, has implications for lowering microbial protein synthesis. In this study, both occurrences were confirmed in the plant materials with high tannin contents.…”
Section: In Vitro Rumen Fermentation Bacteria and Protozoal Population Characteristicsmentioning
confidence: 99%